27.0k views
5 votes
4x=−3y−10 9x+2y=6 systems of equations by Elimination... 25 Pts!!

User LouieC
by
5.4k points

2 Answers

7 votes
x = 2 y = -6
add 3y to 4x
User Uclydde
by
5.7k points
3 votes
4x = -3y - 10
9x + 2y = 6

Let us make those in the same format.

4x + 3y = -10
9x + 2y = 6

We need to make the y's or x's to be the same so, because of elimination, we can get rid of one.


8x + 6y = -20
27x + 6y = 18

Subtract them.....

-19x = -38

x = 2

Now plug in 2 for x in one of the equations.

4(2) = -3y - 10

8 = -3y - 10

18 = -3y

-6 = y

(2, -6) is your answer! :)





User Jcelgin
by
6.2k points